Negotiating Islamic Authority in Digital Public Space: Audience Contestation of Ustaz Evie Effendi’s “Misguided Prophet” Lecture on YouTube - Muhammad Roni (Journal of Indonesian Digital Islamic Studies, 2026)
The digitalization of religion has destabilized traditional authority structures, fostering a shift from institutional lineage to algorithmic legitimacy. This study investigates the contestation of religious authorities regarding Ustaz Evie Effendi’s controversial “Misguided Prophet” lecture on YouTube. Employing a netnographic methodology and Heidi Campbell’s Digital Religion framework, this research analyzes public discourse within comment sections to understand how theological meaning is negotiated online. The findings indicate a transformation of prophetic ta’zīm (reverence), where digital expressions of piety function simultaneously as theological markers and instruments of authority legitimation. The study argues that social media platforms serve as horizontal epistemic fields in which audiences actively validate or reject religious claims, thereby disrupting preachers’ “algorithmic authority.” Ultimately, this research sheds light on how digital contestation reconfigures the dynamics of Islamic leadership, underscoring the need for epistemic accountability in an era where religious truth is increasingly shaped by participatory engagement rather than scholarly consensus.